Driving Organizational Innovation in Public Healthcare: The Strategic Impact of Inclusive Leadership - Qureshi, Saba Feroz; Tasneem, Khawaja Asif (European Scientific Journal, ESJ, 2024)
In the public sector, it is essential to prioritize innovation and adaptation to efficiently tackle intricate and ever-changing difficulties. The objective of this study is to analyze how inclusive leadership affects the innovative work behavior of employees in the public healthcare sector and to determine the function of public service motivation and leader-member exchange theory in regulating this relationship. To evaluate the study’s hypotheses, data was collected from a field study of 300 public healthcare workers. The data was gathered via structured surveys and analyzed using Hayes’ technique with the help of Mplus. The testing was combined with bootstrapping to analyze mediation and moderation relationships in the study. The results show a strong and positive connection between inclusive leadership and employees’ innovative work behavior in the public healthcare sector. Furthermore, the variables of autonomy and competence played a mediating role in the connection between inclusive leadership and individual work behavior. The study also includes a rigorous investigation of its results, as well as an analysis of their implications, limitations, and recommendations for future research endeavors.